Sex differences in clinical presentation in acute MI - Kodliwadmath, Ashwin; Nimbal, Naren V. (International Journal of Advances in Medicine, 2017)
Background: Acute myocardial infarction differs in women and men with respect to risk factors and clinical presentation. There are studies carried out worldwide on this issue but few from India. This study was done to study the sex based differences in the risk factors and clinical features of acute MI in patients with Indian ethnicity. Methods: Comparative prospective study consisting of 100 women as study group and 100 men as control group with acute MI, who were admitted in a tertiary care hospital, from December 2016 to June 2017. Results: Chest pain was the main complaint in majority of the women (82%) and men (88%). Radiation of chest pain (87%) and sweating (90%) were significantly present in men compared to women (65% and 62% respectively), while breathlessness was significantly present in women (78%) compared to men (64%) and fatigue in women (76%) significantly more than men (55%). Smoking was a significant risk factor in men (69%) compared to women (5%), while diabetes mellitus was a significant risk factor in women (62%) compared to men (39%). Conclusions: Women with acute MI had more atypical presentation of symptoms, similar risk factors, compared to men except for smoking which was more significant in men and diabetes more common in women.